Déjà vu experiences in anxiety. Issue 7 (9th August 2021) - Wells, Christine E.; O'Connor, Akira R.; Moulin, Chris J. A.
ABSTRACT: Déjà vu occurs when a novel event is experienced with an erroneous sense of familiarity. Memory researchers theorise that this arises due to an error in the processes underlying the recognition memory system. Research has indicated that there may be a link between high levels of anxiety and increased frequency and intensity of déjà vu, however, there has been a comparatively little characterisation of déjà vu as experienced by individuals with clinical anxiety. We used an online questionnaire to collect data from individuals self-reporting a clinical diagnosis of anxiety, as well as from age-matched controls. The Anxiety Group reported a significantly higher frequency of déjà vu episodes over the previous month than controls. They also reported experiencing déjà vu more frequently and with higher intensity during periods of high anxiety. In addition, the Anxiety Group reported finding déjà vu episodes significantly more distressing than the Control Group. The findings indicate that there are differences in déjà vu experienced by people reporting high levels of anxiety compared to healthy controls without an anxiety diagnosis. We discuss structural and neural mechanisms thought to underpin déjà vu in relation to these results.